Explore a diverse range of topics and get expert answers on IDNLearn.com. Discover detailed answers to your questions with our extensive database of expert knowledge.
Sagot :
A second-degree equation that can be written in the form [tex]\( ax^2 + bx + c = 0 \)[/tex], where [tex]\( a \)[/tex], [tex]\( b \)[/tex], and [tex]\( c \)[/tex] are real numbers and [tex]\( a \neq 0 \)[/tex], is called a quadratic equation.
Let's illustrate the solution with an example:
Consider the quadratic equation [tex]\( 2x^2 + 3x + 1 = 0 \)[/tex] where [tex]\( a = 2 \)[/tex], [tex]\( b = 3 \)[/tex], and [tex]\( c = 1 \)[/tex].
To find the solutions (roots) of the quadratic equation, we can use the quadratic formula:
[tex]\[ x = \frac{-b \pm \sqrt{b^2 - 4ac}}{2a} \][/tex]
First, compute the discriminant [tex]\( \Delta \)[/tex] which is given by [tex]\( b^2 - 4ac \)[/tex]:
[tex]\[ \Delta = 3^2 - 4(2)(1) = 9 - 8 = 1 \][/tex]
The discriminant is 1. Since the discriminant is greater than 0, we have two distinct real roots. We can now find the roots.
For the first root:
[tex]\[ x_1 = \frac{-b + \sqrt{\Delta}}{2a} = \frac{-3 + \sqrt{1}}{2(2)} = \frac{-3 + 1}{4} = \frac{-2}{4} = -0.5 \][/tex]
For the second root:
[tex]\[ x_2 = \frac{-b - \sqrt{\Delta}}{2a} = \frac{-3 - \sqrt{1}}{2(2)} = \frac{-3 - 1}{4} = \frac{-4}{4} = -1 \][/tex]
Thus, the roots of the quadratic equation [tex]\( 2x^2 + 3x + 1 = 0 \)[/tex] are [tex]\( -0.5 \)[/tex] and [tex]\( -1 \)[/tex], and the discriminant is [tex]\( 1 \)[/tex].
Let's illustrate the solution with an example:
Consider the quadratic equation [tex]\( 2x^2 + 3x + 1 = 0 \)[/tex] where [tex]\( a = 2 \)[/tex], [tex]\( b = 3 \)[/tex], and [tex]\( c = 1 \)[/tex].
To find the solutions (roots) of the quadratic equation, we can use the quadratic formula:
[tex]\[ x = \frac{-b \pm \sqrt{b^2 - 4ac}}{2a} \][/tex]
First, compute the discriminant [tex]\( \Delta \)[/tex] which is given by [tex]\( b^2 - 4ac \)[/tex]:
[tex]\[ \Delta = 3^2 - 4(2)(1) = 9 - 8 = 1 \][/tex]
The discriminant is 1. Since the discriminant is greater than 0, we have two distinct real roots. We can now find the roots.
For the first root:
[tex]\[ x_1 = \frac{-b + \sqrt{\Delta}}{2a} = \frac{-3 + \sqrt{1}}{2(2)} = \frac{-3 + 1}{4} = \frac{-2}{4} = -0.5 \][/tex]
For the second root:
[tex]\[ x_2 = \frac{-b - \sqrt{\Delta}}{2a} = \frac{-3 - \sqrt{1}}{2(2)} = \frac{-3 - 1}{4} = \frac{-4}{4} = -1 \][/tex]
Thus, the roots of the quadratic equation [tex]\( 2x^2 + 3x + 1 = 0 \)[/tex] are [tex]\( -0.5 \)[/tex] and [tex]\( -1 \)[/tex], and the discriminant is [tex]\( 1 \)[/tex].
We value your participation in this forum. Keep exploring, asking questions, and sharing your insights with the community. Together, we can find the best solutions. Find precise solutions at IDNLearn.com. Thank you for trusting us with your queries, and we hope to see you again.